Strategy In Preventing Financial Distress: Resolution Of Problem Financing At Bank Aceh Syariah Branch Peureulak Aceh - Ulya, Zikriatul; Safwandi; Sarita Ulfia; Muarif Setiawan; Zulhilmi (IAIN Langsa, 2025)
This study discusses the strategy of resolving problematic financing in preventing financial distress at Bank Aceh Syariah sub-branch peureulak, the problems presented in this study are, the level of financing problems in Bank Aceh Syariah sub-branch of peureulak how to solve problematic financing in preventing financial distress at Bank Aceh Syariah Peureulak auxiliary branch, what decisions are taken in the settlement of problematic financing, what are the strategies in the settlement of problematic financing. The purpose of this study is to analyze the strategy for resolving problematic financing in preventing financial distress at Bank Aceh Syariah sub-branch peureulak with a process hierarchy analysis method. This research method is the positive qualitative Analytic Hierarchy Process (AHP) method. The results of this study show that the alternative priority of problematic financing settlement strategies in preventing financial distress at Bank Aceh Syariah sub-branch peureulak from the results of the assessment of 3 criteria, 5 sub-criteria, and 4 alternatives based on the results of the analysis of AHP using expert choice The highest priority strategy is to close and sell one or more business units (0.293), then the second strategy priority is the extension of the credit schedule (0.280), and the third strategy is to reduce profits (0.231). In conclusion, the priority of alternative strategies for resolving problematic financing in preventing financial distress at Bank Aceh Syariah sub-branch of peureulak from the results of the assessment of 3 criteria, 5 sub-criteria, and 4 alternatives based on the results of the analysis using expert choice obtained is the highest priority of the third-party fund dependency strategy with an inconsistency value of 0.05< 0.1 interpreted as consistent. The recommendation for banks is to strengthen risk analysis and financing restructuring policies, while for customers, it is recommended to be cooperative in following financing rescue policies so that business sustainability is maintained and the risk of financial distress can be minimized.